5-minute chair yoga for seniors : simple exercises to improve mobility and reclaim your confidence - Dolezal, Kierstie Payge (Sasquatch Books, 2025)
"Yoga teacher Kierstie Payge Dolezal ... offers a gentle, uplifting way to reconnect with your body, reduce pain and stiffness, and build strength and flexibility. ... Inside you'll find: 45 simple exercises you can do using a sturdy chair, 9 complete sequences for quick daily routines, ... modifications for all ability levels, mindfulness techniques to calm the nervous system, [and] tips to create your own personalized daily practice"--Page 4 of cover.